Trends in organ donation and transplantation over the past eighteen years in Iran. Issue 2 (2nd January 2023) - Shadnoush, Mahdi; Latifi, Marzieh; Rahban, Habib; Pourhosein, Elahe; Shadnoush, Alireza; Jafarian, Arefeh; Dehghani, Sanaz
Abstract: Background: This article will review the trends in organ donation over the past 18 years in Iran. Material and methods: All donation and transplantation statistics were extracted by reviewing the Organ Procurement and Transplantation database of the Ministry of Health of Iran from 2002 to 2019. Results: Iran's national deceased donation rate from 2002 to 2019 increased 19.06‐fold from .75 to 14.3 per million population (PMP). After the beginning of the COVID‐19 pandemic, the rate of organ donation in Iran decreased significantly. Although 1 year after the onset of the pandemic, due to the widespread adoption of COVID19 vaccination, the rate of organ donation began to increase again, this system is still under performing. During the years under examination, the rate of deceased kidney donation increased significantly compared to living kidney donation and reached up to 2001 kidney transplantations in 2021. From 2002 to 2019, the rate of liver transplants increased to 12.8. Likewise, the rate of heart transplants increased 8.4‐fold, from 15 to 126 cases during the same time. Conclussion: Although a personal choice, the process of organ donation involves medical, legal, ethical, organizational, and social aspects. The trend in increasing donation rates over the past years can be attributed to multiple influences, which include rigorous team efforts in the organ donation and transplantation systems, in addition to creating a donation culture and promoting donation through media platforms. Moreover, we can say that the rising rates of deceased donor transplantation also can drive down rates of commercial living donor transplantation.